The Influence of Overhead Cranes in the Seismic Performance of Industrial Buildings - Belleri, Andrea; Labò, Simone; Marini, Alessandra; Riva, Paolo (Frontiers in Built Environment, 2017)
The paper investigates the influence of overhead cranes with a hanging mass under earthquake type loading, considering the Emilia 2012 seismic sequence. The structural layout of precast concrete industrial buildings typical of the Italian territory is considered. The equations of motion describing the behaviour of the hoist load are derived and a sensitivity analysis is carried out on simplified three degrees of freedom systems by solving the governing differential equations. The influence of various parameters on the roof displacement and on the horizontal load transferred by the hanging mass is addressed. The considered parameters are the relative damping of the hanging mass, the length of the hoist ropes, the earthquake record, the hysteretic type of the plastic hinges at the column base, and the behaviour factor of the structural system. The results show that for a horizontal component of the considered seismic sequence the structural displacements are amplified in the case of a behaviour factor greater than 2.5. A simplified modelling strategy considering small displacements is also investigated. Such model is suitable for response spectrum analyses. Finally, a three-dimensional case study is analysed by means of non-linear time history analyses. The results show the influence of the overhead crane on the local performance of some structural and non-structural elements, such as columns and cladding panels, especially when the assumption of rigid roof diaphragm does not apply.